Influence of the type of salt-forming acids on the antiradiation activity of T1023 analogs – salts of N-isobutanoyl-S-isopropylisothiourea - M. V. Filimonova; A. S. Saburova; L. I. Shevchenko; V. M. Makarchuk; A. A. Lychagin; A. S. Filimonov (Радиационная гигиена)
According to leading experts, the vast arsenal of radioprotective agents available in the world today does not fully meet modern practical needs, both in the field of radiation protection, and in the prevention and treatment of complications of radiotherapy. The purpose of the study was to evaluate the effect of the salt-forming acids type on the radioprotective activity of NOS inhibitor T1023. The chemical part of this study included methods of chemical synthesis, physicochemical and elemental analysis. Pharmacological part – assessment of acute toxicity using V.B. Prozorovsky express method and the study of radioprotective activity using Till and McCulloch method based on the ability of mice hematopoietic cells to form spleen colonies after irradiation. The number of endogenous hematopoietic spleen colonies were assessed on the 8th day after total exposure to gamma-irradiation at a dose of 6 Gy in six independent experiments. As a result of directed chemical synthesis, six new derivatives of T1023 – salts of N-isobutanoyl-S-isopropylisothiourea have been developed, identified and characterized. The results of studying the safety and radioprotective activity of the synthesized compounds showed that changes in the salt-forming acid don’t significantly influence the toxicity: all studied compounds are in the 3rd class of toxicity and hazard. At the same time, it was found that the replacement of the salt-forming acid significantly influenced the severity of the radioprotective effect. For some of these compounds radioprotective efficacy is comparable to or exceeds the efficacy of the initial compound T1023. It is important to note that these new compounds were used in lower, more save doses than T1023. The results suggest promising further development of NOS inhibitors – isothiourea derivatives as radioprotective agents.